Dependability and Security Will Change Embedded Computing. - Serpanos, Dimitrios; Henkel, Jörg (Computer (00189162), 2008)
The article reports on embedded computing systems. These systems are found in many places, from automobiles to entertainment gadgets and, as such, reliability and durability are necessary in the architecture, design, and development methodologies. Future designs must look more closely at dependability, security, and safety to insure the efficiency of embedded computing systems. Microminiaturization has lessened the control designers have over the fabrication process and have increased the number of defective on-chip devices. With the decrease in feature size the development of efficient low-power security engines is more difficult.